DETERMINANTS OF HEALTH INSURANCE CHOICE IN KENYA - Kiplagat, Isabella; Muriithi, Moses; Kioko, Urbunus (European Scientific Journal, ESJ, 2013)
In Kenya, the out-of-pocket health expenditure by households accounts for around 36 percent of the total expenditure on health. A Large out-of-pocket payment is known to reduce consumption expenditure on other goods and services and thus pushing households into poverty through catastrophic expenditure. Recent studies have shown that health insurance can be used to mitigate impoverishing effects of large out-of-pocket health expenditure. In Kenya, health insurance has limited coverage, yet there are various types of health prepayment schemes. This paper explores the determinants of choice of health insurance schemes in Kenya. Utilizing the 2008-2009 Kenya Demographic Health Survey (KDHS), a multinomial logit model is estimated. The findings is that wealth index, employment status, education level and household size are important determinants of health insurance ownership and choice. Also, lack of awareness prevents many from enrolling in any form of health insurance scheme.